2018
DOI: 10.1055/s-0037-1609913
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)-Catalyzed Redox-Neutral Cyclizations of Alkynes Containing Alkenyl or Electrophilic Functional Groups: A Convenient Synthesis of Carbocycles and Heterocycles

Abstract: The palladium(II)-catalyzed redox-neutral cyclizations of alkynes bearing alkenyl or electrophilic functional groups, such as carbonyl, imino, or cyano groups, were developed to provide convenient approaches to various carbocycles and heterocycles. These tandem reactions are initiated by nucleopalladation of alkynes, transmetalation of arylboron reagents with palladium, or hydropalladation of alkynes, and they are quenched by β-heteroatom elimination, addition to electron-deficient alkenes, or addition to carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Over the past decade, significant advances have been made in the development of palladium-catalyzed redox-relay Heck-type processes by Sigman's group and others, in which the double bond migrates along the alkyl chain by iterative β-hydride elimination/migratory insertion steps until captured by the alcohol moiety. 7 Inspired by the success of these achievements, we envisaged that the combination of Pd( ii )-catalyzed cyclization of alkynes 8 and the redox-relay Heck arylation of alkenols might offer a novel convergent cascade reaction to access tetrahydro-β-carbolines and their analogs. We surmised that 2-(hydroxyenynyl)sulfonanilides could engage in sequential electrophilic cyclization and redox-relay Heck cyclization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decade, significant advances have been made in the development of palladium-catalyzed redox-relay Heck-type processes by Sigman's group and others, in which the double bond migrates along the alkyl chain by iterative β-hydride elimination/migratory insertion steps until captured by the alcohol moiety. 7 Inspired by the success of these achievements, we envisaged that the combination of Pd( ii )-catalyzed cyclization of alkynes 8 and the redox-relay Heck arylation of alkenols might offer a novel convergent cascade reaction to access tetrahydro-β-carbolines and their analogs. We surmised that 2-(hydroxyenynyl)sulfonanilides could engage in sequential electrophilic cyclization and redox-relay Heck cyclization.…”
mentioning
confidence: 99%
“…Removing LiCl (entry 13) or the phosphine ligand (entry 14) reduced the yield of 2a , which indicated that the potential chelation of chloride might stabilize the indolyl palladium intermediate. 8 In the absence of the palladium catalyst, no reaction was observed (entry 15).…”
mentioning
confidence: 99%
“…Palladium-catalyzed enyne cyclization initiated by nucleopalladation of alkynes represents a synthetically appealing approach for the synthesis of structurally diverse carbocycles or heterocycles in a high step-economy fashion . During this process, alkynes could react with various nucleophiles and generate diverse vinylpalladium species, which are prone to Heck-type insertion with alkenes (Scheme a) .…”
mentioning
confidence: 99%
“…Intramolecular oxypalladation of alkynoic acid derivatives and sequential addition to electrophiles (e.g., carbonyls, α, β-unsaturated compounds) have been established as a powerful tool to construct condensed oxygen-containing heterocycles . Palladium-catalyzed annulations of ortho -alkynylbenzoates to afford isocoumarin scaffolds were reported by Lu, Li, Jiang, Sridharan, and others .…”
mentioning
confidence: 99%